McCune-Albright syndrome and the extraskeletal manifestations of fibrous dysplasia - Collins, Michael T (BioMed Central, 2012)
Fibrous dysplasia (FD) is sometimes accompanied by extraskeletal manifestations that can include any combination of café-au-lait macules, hyperfunctioning endocrinopathies, such as gonadotropin-independent precocious puberty, hyperthyroidism, growth hormone excess, FGF23-mediated renal phosphate wasting, and/or Cushing syndrome, as well as other less common features. The combination of any of these findings, with or without FD, is known as McCune-Albright syndrome (MAS). The broad spectrum of involved tissues and the unpredictable combination of findings owe to the fact that molecular defect is due to dominant activating mutations in the widely expressed signaling protein, G(s)α, and the fact these mutations arises sporadically, often times early in development, prior to gastrulation, and can distribute across many or few tissues. The complexity can be mastered by a systematic screening of potentially involved tissues and cognizance that the pattern of involved tissues is established, to some degree, in utero. Thorough testing allows the clinician to establish, often times at presentation, the full extent of the disease, and importantly as well what tissues are unaffected. Treatment and follow-up can then be focused on affected systems and a meaningful prognosis can be offered to the patient and family. The authors outline screening and treatment strategies that allow for effective management of the extraskeletal manifestations of FD.